4c+6=-5(1-3c)

Simple and best practice solution for 4c+6=-5(1-3c) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4c+6=-5(1-3c) equation:


Simplifying
4c + 6 = -5(1 + -3c)

Reorder the terms:
6 + 4c = -5(1 + -3c)
6 + 4c = (1 * -5 + -3c * -5)
6 + 4c = (-5 + 15c)

Solving
6 + 4c = -5 + 15c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-15c' to each side of the equation.
6 + 4c + -15c = -5 + 15c + -15c

Combine like terms: 4c + -15c = -11c
6 + -11c = -5 + 15c + -15c

Combine like terms: 15c + -15c = 0
6 + -11c = -5 + 0
6 + -11c = -5

Add '-6' to each side of the equation.
6 + -6 + -11c = -5 + -6

Combine like terms: 6 + -6 = 0
0 + -11c = -5 + -6
-11c = -5 + -6

Combine like terms: -5 + -6 = -11
-11c = -11

Divide each side by '-11'.
c = 1

Simplifying
c = 1

See similar equations:

| 2n/9m-n/2 | | 9x3-9x(-20/5) | | 5(5x-8)=3(11x-9) | | 3y+10y=7 | | 5+2x=60 | | 41.83+w=446.45 | | 3t^2-14t+32=0 | | y-2z=0 | | X*2+12x-1=0 | | z=32+4(-3) | | -2x+9.3=-4.7 | | 6w^2-78w+216= | | 124=23h+42 | | 140.93x^3+1776.67X^2-7000=0 | | 3c=5c+21 | | 2(1/2)= | | 3x-8=-4x-12 | | x-41=-15 | | 8x/-8x | | m=32+4/7-5 | | 2y-5+2y-5+y^2-62=180 | | 4x-20-5=6+7.4-4x | | 3k-4-7k=8 | | 2x+109+89=180 | | .5(4x-2)=2x-2 | | 4x-29-5=6+7.4-4x | | 4x-3x+15=14-4 | | 27.8=4(21.2)+y | | -13+3x=-39+13x | | x^2+4.05x-.8019=0 | | 10x-45=150-1x | | 9-z+1=-3(z+2) |

Equations solver categories